Recommended Optimization Efforts to Improve Traffic Offenders Compliance in the Resolution of Electronic Traffic Law Enforcement (ETLE) in Padang City - Alpino, M. Owen; Malau, Hasbullah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by the fact that although the implementation of ETLE aids in traffic law enforcement, the aspect of traffic violators compliance with ETLE ticket resolution still requires further investigation, considering the challenges in encouraging traffic violators to actively resolve their violations through the ETLE system. This research aims to identify optimization efforts that can be recommended to improve traffic violators' compliance in settling ETLE in Padang City. This research uses a descriptive qualitative approach, with data obtained from observations, interview results, and documents related to ETLE. The optimization efforts use indicators from Siringoringo (2005), namely objectives, decision alternatives, and limited resources. The research results show that the level of compliance among traffic violators is still low, where the violators comply only to avoid harsher penalties, not out of awareness that resolving ETLE is something done voluntarily and believed to be good for them, the violators. Then there are several administrative obstacles found in the resolution of ETLE tickets. The recommended optimization efforts are (1) Conducting intensive socialization to the public regarding the technical implementation of ETLE fines, (2) Implementing a program for periodic correction and updating of vehicle address data, (3) Imposing additional fines on violators who do not promptly settle ETLE fines, (4) Upgrading CCTV cameras with Face Recognition features, and (5) Digitizing the delivery of confirmation letters. So, the delivery of confirmation letters can be done by sending them through the violator's phone number or via the violator's email.